2012
DOI: 10.1515/jbcpp-2012-0001
|View full text |Cite
|
Sign up to set email alerts
|

Acute myocardial infarction (AMI) (n-11026) on days of zero geomagnetic activity (GMA) and the following week: differences at months of maximal and minimal solar activity (SA) in solar cycles 23 and 24

Abstract: Zero-GMA/high-neutron activity is followed by increase in AMI admissions at the days that follow. The effects are different at high and low parts of the 11-year solar cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Lithuanian researchers in another study have found correlation between heart rate variability and geomagnetic field strength, their study has shown that autonomic nervous system responds to solar and geomagnetic activity [ 21 , 22 , 23 ]. Moreover, in another study which included patients from Lithuania, researchers found out that number of acute myocardial infarction events after low geomagnetic field activity and high cosmic rays days increased by a fifth, their obtained results indicate that geomagnetic field may be related to development of myocardial infarction [ 24 , 25 ]. Our study results indicate that the effects of changes in local geomagnetic field should be studied analyzing field’s strength in frequency ranges.…”
Section: Discussionmentioning
confidence: 99%
“…Lithuanian researchers in another study have found correlation between heart rate variability and geomagnetic field strength, their study has shown that autonomic nervous system responds to solar and geomagnetic activity [ 21 , 22 , 23 ]. Moreover, in another study which included patients from Lithuania, researchers found out that number of acute myocardial infarction events after low geomagnetic field activity and high cosmic rays days increased by a fifth, their obtained results indicate that geomagnetic field may be related to development of myocardial infarction [ 24 , 25 ]. Our study results indicate that the effects of changes in local geomagnetic field should be studied analyzing field’s strength in frequency ranges.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of evidence that GMD affects the human health. The associations between GMD and increased risk of myocardial infarction, suicide, and stroke have been reported, previously [ 3 7 ]. In spite of primary suggestions by some researchers in the past decades [ 8 , 9 ], we found that this issue as a possible environmental risk factor for MS has been neglected, and no comprehensive hypothesis has been designed to explain the potential relationship between GMD and MS.…”
Section: Introductionmentioning
confidence: 71%
“…Some studies have shown that ANS (automatic nervous system) responds to solar and geomagnetic activity [34][35][36]. Stoupel and Collegues [37,38] also found out that number of acute MI events after low GMF activity and high CRs days of increased their obtained results indicate that GMF can be related to development of MI. These investigations indicate that the effects of variations in GMF should be studied by analyzing the strength of fields in frequency ranges.…”
Section: Influens Of Fluctuations In the Space Weather On The Chronop...mentioning
confidence: 80%